Teacher Management in Integrated Islamic School - Sukirdi, Sukirdi; Sujanto, Bedjo; Hanafi, Ivan (International Journal for Educational and Vocational Studies, 2019)
This study aims to find, to describe, and to inform about the management of teachers at SDIT Iqra 1 Bengkulu. This research used a qualitative approach by using a case study method. The data was  collected by observation, interview, and documentation techniques. The data analysis used interactive analysis start from: data collection, data presentation, data reduction, and collection conclusion. The results of this study contain patterns of teacher training and development at SDIT Iqra 1 Bengkulu which are different from commonly schools. The differences are in:The difference are selection of applicants written and unwritten, and interviews In addition, the differences in training and development include two the main aspects are aspects of training and development of education and religious knowledge which is carried out continuously for all teachers ranging from school principals to ordinary teachers with the pattern of forming training and development groups.